Experimental investigations of 3.75 kW laboratory scale pico Kaplan hydraulic turbine - Shiv Lal; Shanti Lal Meena (International Journal of Applied Power Engineering (IJAPE), 2023)
Experimental investigations of 3.75 kW Pico Kaplan turbines have been carried out in this communication. The turbine is utilized for the experimental purpose for the students and it is procured under TEQIP-III project of World Bank. The load test of the turbine has been done which run at 50% capacity and presented the main and operating characteristic curves. It is observed that the efficiency of the turbine will improve at low speed, high brake power and high discharge. The discharge is also depending on the available head and the quantity of water. So, the turbine efficiency is also improved with respect to increasing the discharge.  At the increasing the specific speed the discharge will also be increased linearly. The Pico Kaplan turbine can be used for runways water likes in Canals, rivers and no dam is required. The basic design is very simple and it is very common because it has vast applications for small, pico and micro power generation. It can be used in lot of regions like Himachal, Uttarakhand, Jammu & Kashmir, Eastern State (Assam, Arunachal Pradesh, Meghalaya, and Manipur), Punjab, Karnataka, Kerala, West Bengal, Maharashtra and Rajasthan states of India. This study will be useful for the researcher in the area of small hydro power plants.